(3GSJQGJjLjGJ GdUQGY GdOhdj(B. s (3GdcJGH GdKGdK,s (3eaGgje GdYdGbGJ GdOhdjI (B: (3GdJNWjW GdGSJQGJjLj dJMbjb GdCef (B/s - (3YhOI, LgGO MQHs ((3GdbGgQI ;s (3GdchjJ ;s (3GdLRGFQ (B:s (3OGQ GdcJGH GdMOjK ddWHY hGdfTQ hGdJhRjY,s, 2016)
(3jJfGhd cJGH (B((3eaGgje GdYdGbGJ GdOhdjI (B: (3GdJNWjW GdGSJQGJjLj dJMbjb GdCef(B) (3hGdPj bGe HJCdjag (B((3C(B. (3O(B. (3LgGO YhOI(B) (3aj MhGdj (B(899 (3UaMI(B) (3ef GdbWY GdeJhSW ehVhY (B((3GdCef GdOhdj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdcJGH GdKGdK (B: (3eaGgje GdYdGbGJ GdOhdjI (B: (3GdJNWjW GdGSJQGJjLj dJMbjb Gdef, GdaUd GdJGSY (B: (3eONd ddUQGY GdOhdj hGdEbdjej aj TQb GdeJhSW, GdaUd GdYGTQ (B: (3GdUQGYGJ GdJj JhdOgG GdHjFI GdeMdjI GdYhdejI(B... (3EdN(B.s
(3GdecJHI jJhGaQ HgG (B: (3eLdO (B3.s
(3HHdjhLQGajI (B: (3UaMI (B896-899.s
Keywords: (3GdSjGSI GdOhdjIs; (3GdYdGbGJ GdNGQLjIs; (3GdCef GdOhdjs